2023
DOI: 10.1097/md.0000000000034379
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation and the clinical significance of KCNQ1OT1 and HAGLROS lncRNAs in papillary thyroid cancer: An observational study

Abstract: Long noncoding RNAs (lncRNAs) play an important role in regulating gene expression. Changes in their expression have been associated with many types of cancer, including thyroid cancer. This study aimed to investigate how changes in the expression of potassium voltage-gated channel subfamily Q member 1 opposite strand/antisense transcript 1 (KCNQ1OT1) and HAGLR opposite strand lncRNA (HAGLROS) lncRNAs correlate with the development and clinicopathological characteristics of papillary thyroid cancer (PTC). Reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that HAGLROS promotes the malignant progression of gastric cancer cells, suggesting that HAGLROS may be a malignant factor in cancer [ 21 ]. In addition, recent studies have shown that HAGLROS is highly expressed in PTC clinical samples [ 22 ]. However, its role and mechanism in PTC are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that HAGLROS promotes the malignant progression of gastric cancer cells, suggesting that HAGLROS may be a malignant factor in cancer [ 21 ]. In addition, recent studies have shown that HAGLROS is highly expressed in PTC clinical samples [ 22 ]. However, its role and mechanism in PTC are still unclear.…”
Section: Discussionmentioning
confidence: 99%